2022
DOI: 10.1007/s10858-022-00395-z
|View full text |Cite
|
Sign up to set email alerts
|

Towards autonomous analysis of chemical exchange saturation transfer experiments using deep neural networks

Abstract: Macromolecules often exchange between functional states on timescales that can be accessed with NMR spectroscopy and many NMR tools have been developed to characterise the kinetics and thermodynamics of the exchange processes, as well as the structure of the conformers that are involved. However, analysis of the NMR data that report on exchanging macromolecules often hinges on complex least-squares fitting procedures as well as human experience and intuition, which, in some cases, limits the widespread use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Lineshape fitting methods can also be applied to parametric estimation problems separate from chemical exchange, for example in the analysis of methyl side-chain dynamics by fitting 1 H-coupled 13 C multiplets to determine cross-correlated relaxation rates [79]. There is the potential for these methods to be coupled with automated, optimal acquisition protocols [80], and for the application of machine learning methods to accelerate the interpretation of NMR observations [81]. Thus, we are confident that this technique has a bright future that will find increasing applications across a variety of chemical and biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…Lineshape fitting methods can also be applied to parametric estimation problems separate from chemical exchange, for example in the analysis of methyl side-chain dynamics by fitting 1 H-coupled 13 C multiplets to determine cross-correlated relaxation rates [79]. There is the potential for these methods to be coupled with automated, optimal acquisition protocols [80], and for the application of machine learning methods to accelerate the interpretation of NMR observations [81]. Thus, we are confident that this technique has a bright future that will find increasing applications across a variety of chemical and biological systems.…”
Section: Discussionmentioning
confidence: 99%
“…As described previously, the output from each layer is combined to give the final output and also added to the input for the residual unit to form the input for the next layer. For the 13 C network, the dilations employed are cycled through the values: 1,2,4, 6,8,10,12,14,16,20,24,28,32,40,48,56,64, and there are 128 filters for each convolutional layer. For the 1 H network the dilations employed are 1,2,4,6,8,10,12,14,16,20,24,28,32, and there are 64 filters per convolutional layer.…”
Section: The Network Architecture and Trainingmentioning
confidence: 99%
“…For the 13 C network, the dilations employed are cycled through the values: 1,2,4, 6,8,10,12,14,16,20,24,28,32,40,48,56,64, and there are 128 filters for each convolutional layer. For the 1 H network the dilations employed are 1,2,4,6,8,10,12,14,16,20,24,28,32, and there are 64 filters per convolutional layer.…”
Section: The Network Architecture and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this era of burgeoning applications and developments in AI, from computational structural biology 4,5 to sophisticated large language models 6 , it is natural to look for solutions within this field for the challenges encountered in characterising large proteins. In this context, we and others have recently demonstrated that deep neural networks (DNNs) can be trained to accurately transform [7][8][9] and analyse [10][11][12] complex NMR data. The most recent applications use supervised deep learning, where a DNN is supplied with an input and a target training dataset and through a training process the DNN attempts to determine the mapping between the two.…”
mentioning
confidence: 99%